Population fluctuations of Gynaikothrips ficorum (Marchal, 1908) (Thysanoptera, Tubulifera) and natural enemies on leaf gall of Ficus retusa in Algeria - K. Ziouani; A. Benzehra; L. Saharaoui (Arxius de Miscel-lània Zoològica, 2019)
Fluctuacions en les poblacions de Gynaikothrips ficorum (Marchal, 1908) (Thysanoptera, Tubulifera) i dels seus enemics naturals a les gales de fulles de Ficus retusa a Algèria